Scanning time prediction method and device, storage medium and electronic equipment - SHAO CHUANG; FENG YONG; JING SHIJIA (2019)
The invention provides a scanning time prediction method and device, a storage medium and electronic equipment, which are used for for reasonably setting the scanning time of a subject for PET-CT examination. The scanning time prediction method is used in a PET-CT system, and the method comprises the following steps: acquiring personal information of a subject and an examination part of the subject for PET-CT examination; determining the dosage of a medicament required to be injected for the PET-CT examination of the subject; inputting the personal information, the examination part and the medicament dosage into a trained scanning time model; and obtaining the scanning time, which is predicted by the scanning time model, required by the PET-CT examination of the subject. 本申请提供一种扫描时间的预测方法、装置、存储介质及电子设备，用以合理设置受检者进行PET-CT检查的扫描时间，该扫描时间的预测方法用于PET-CT系统中，该方法包括：获取受检者的个人信息和所述受检者进行PET-CT检查的检查部位；确定所述受检者进行PET-CT检查所需要注射的药剂剂量；将所述个人信息、所述检查部位和所述药剂剂量输入到已训练的扫描时间模型；获得通过所述扫描时间模型预测出的所述受检者进行PET-CT检查所需要的扫描时间。